Theosophical elements in Iqbal's Magnum Opus "the reconstruction of religious thought in Islam": a preliminary review - Hassan Mydin, Shaik Abdullah; Abdul Razak, Mohd Abbas; M M Yusoff, Mahathir (IIUM Press, 2022)
This article reviews the phenomenon of New Atheism and its connection to the sociocultural changes of the twenty first century as well as influences brought by the advent of the information age, especially on the millennial generations. The study argues that the New Atheism was a movement that became part of a world-wide social engineering project referred to by some as the second renaissance. The modern renaissance has identifiable markers similar to the European colonization missions around the world in the eighteenth and nineteenth centuries. Although, at the heart of this project is an explicit rejection of a supernatural entity, embedded within it is a tacit rejection of belief in all things in favor of a more empirical approach seated in evidence-based outcomes especially in the area of ethics. The paper argues that the culmination of this project, that is, negation of belief in God or a God-like entity proposed by New Atheism is no longer limited to atheism but has now become a general disposition of indifference to the metaphysical realm. The research further argues that a proposition to eliminate belief from the human ethos entails eliminating the faculty of belief itself which is much more destructive to social and ethical foundations of humanity and its area of influence is far greater than just religion. This study is a library-based research and it employs qualitative analysis. Methodology used is based on descriptive, comparative, evaluative and critical analysis from Islamic and Western perspectives.